ChemInform Abstract: Critical Review: Effects of Complex Interactions on Structure and Dynamics of Supported Metal Catalysts. Issue 34 (26th August 2014) - Frenkel, Anatoly I.; Cason, Michael W.; Elsen, Annika; Jung, Ulrich; Small, Matthew W.; Nuzzo, Ralph G.; Vila, Fernando D.; Rehr, John J.; Stach, Eric A.; Yang, Judith C.
Abstract Review: 275 refs.